2011
DOI: 10.2174/157340811796575281
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic Proteases of Human Pathogenic Fungi are Prospective Targets for the Generation of Novel and Effective Antifungal Inhibitors

Abstract: Fungi can cause life-threatening diseases, particularly in patients with weakened immunological systems. Although treatment options are available for these individuals, dose-limiting toxicity and the appearance of drug-resistant microorganisms are growing problems. Detailed structural and functional characterization of fungal proteases has led to novel insights into the workings of these fascinating catalytic machines. Identification and characterization of proteasemediated processes in human pathogenic fungi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 235 publications
(243 reference statements)
0
15
0
Order By: Relevance
“…Other important mechanism of action is the inhibition of rhizopuspepsin and/or saps, a class of enzymes secreted for R. oryzae and other Rhizopus species [ 24 ]. The results in Figure 3 showed inhibition of proteolytic activity of rhizopuspepsin when Piper essential oils were used, mainly P. hispidum and P. tuberculatum which inhibited 11.8% and 12.05% of enzymatic activity, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Other important mechanism of action is the inhibition of rhizopuspepsin and/or saps, a class of enzymes secreted for R. oryzae and other Rhizopus species [ 24 ]. The results in Figure 3 showed inhibition of proteolytic activity of rhizopuspepsin when Piper essential oils were used, mainly P. hispidum and P. tuberculatum which inhibited 11.8% and 12.05% of enzymatic activity, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, proteolytic enzymes are promising targets for the action of new antifungal drugs, especially aspartic-type proteases that are implicated in several facets of basic biological processes of fungal cells as well as directly participating in numerous events of the interaction of fungal cells with host structures (Fig. 12) [250]. With this appeal, Saps of C. albicans fit these criterions because they are enzymes …”
Section: Discussionmentioning
confidence: 99%
“…Currently, the main approach has been to obtain good inhibitors of the target protease, in the belief that inhibition of the activity will be therapeutic. In this context, our research group has published some works that corroborate this premise [1][2][3][4][5][6]10,[29][30][31][32][33][34][35][36][37][38][39] .…”
Section: Tripeptidyl Peptidases Dipeptidyl Peptidasesmentioning
confidence: 94%
“…Actually, C. albicans possesses ten different SAP genes (SAP1 to SAP10), which are expressed according to distinct environments and host conditions [56][57][58][59][60] . Therefore, Saps are potential targets for the development of novel anti-C. albicans drugs [1,2,34,35] . In this context, several groups have demonstrated that aspartic protease inhibitors, including pepstatin A and the first generation of protease inhibitors used in anti-human immunodeficiency virus (HIV) therapy (nelfinavir, saquinavir, ritonavir and indinavir), are able to restrain Sap activity (especially Sap1, Sap2 and Sap3) as well as arrest crucial events of C. albicans yeast cells such as proliferation and adhesion to both abiotic (e.g.…”
Section: Tripeptidyl Peptidases Dipeptidyl Peptidasesmentioning
confidence: 99%
See 1 more Smart Citation